The Influence of Using Crossword Puzzle Media on Increasing Mastery of English Vocabulary in Junior High Schools - Rufiana Zulfia; Zuhri Efendi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Vocabulary mastery is a crucial element in learning English as a foreign language. This study aims to examine the effectiveness of using crossword puzzles as a teaching tool to improve the English vocabulary mastery of seventh-grade students at SMP Negeri 1 Susoh. This study employed a quantitative approach with a quasi-experimental design (pretest-posttest control-group design). The sample consisted of 59 students selected through cluster sampling, divided into an experimental class (Grade VII C, n = 29) and a control class (Grade VII A, n = 30). Data were collected using a vocabulary proficiency test and analyzed using descriptive statistics and an independent-samples t-test in SPSS. The results of the analysis showed a significant difference in mean post-test scores between the experimental and control classes (t(57) = 7.705; p < 0.001). The mean post-test score for the experimental class was 79.69, significantly higher than the control class’s mean of 65.17. These findings demonstrate that the use of crossword puzzles as a teaching medium significantly improves students’ English vocabulary mastery compared to conventional teaching approaches.